2019
DOI: 10.3390/jcm8071002
|View full text |Cite
|
Sign up to set email alerts
|

Non-Linear Relationship between Anti-Apolipoprotein A-1 IgGs and Cardiovascular Outcomes in Patients with Acute Coronary Syndromes

Abstract: Autoantibodies against apolipoprotein A-I (anti-apoA-I IgGs) are prevalent in atherosclerosis-related conditions. It remains elusive whether they improve the prognostic accuracy of the Global Registry of Acute Coronary Events (GRACE) score 2.0 (GS) in acute coronary syndromes (ACS). In this prospective multicenter registry, 1713 ACS patients were included and followed for 1 year. The primary endpoint (major adverse cardiovascular events (MACE)) was defined as the composite of myocardial infarction, stroke (inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(46 citation statements)
references
References 37 publications
(84 reference statements)
2
38
0
Order By: Relevance
“…Among autoantibodies of interest in CVD, the interest in antibodies against apolipoprotein A-1 (anti-ApoA-1 IgG) appears to be gaining momentum. Indeed, three recent studies derived from a large multicenter general population cohort demonstrated that anti-ApoA-1 IgGs were an independent cardiovascular (CV) risk factor predictive of poor prognosis [3][4][5] similarly to what had been reported previously and more recently in high CV risk populations [6][7][8][9][10][11]. In parallel, translational studies pointed to these autoantibodies as mediators of atherogenesis, promoting atherosclerosis, myocardial necrosis, and mice death through toll-like receptors (TLR) 2,4 and CD14 signaling [12][13][14].…”
Section: Introductionsupporting
confidence: 72%
“…Among autoantibodies of interest in CVD, the interest in antibodies against apolipoprotein A-1 (anti-ApoA-1 IgG) appears to be gaining momentum. Indeed, three recent studies derived from a large multicenter general population cohort demonstrated that anti-ApoA-1 IgGs were an independent cardiovascular (CV) risk factor predictive of poor prognosis [3][4][5] similarly to what had been reported previously and more recently in high CV risk populations [6][7][8][9][10][11]. In parallel, translational studies pointed to these autoantibodies as mediators of atherogenesis, promoting atherosclerosis, myocardial necrosis, and mice death through toll-like receptors (TLR) 2,4 and CD14 signaling [12][13][14].…”
Section: Introductionsupporting
confidence: 72%
“…Multivariate HRs were calculated after adjusting for age, gender, hypertension, diabetes, smoking, BMI, eGFR, HDL and LDL cholesterol, baseline CVD, and ADs. Humoral autoimmunity against apoA1 being known to be relevant for CVD, 2,3,5,8,10,11 sensitivity analyses were performed in primary and secondary prevention subgroups. Secondary prevention individuals were defined by the anamnestic presence of any CAD, any stroke or peripheral artery disease.…”
Section: Methodsmentioning
confidence: 99%
“…During the last decade, evidence has accumulated that autoantibodies against high‐density lipoproteins (HDLs) and their components impact multiple pro‐atherogenic processes, facilitating atherogenesis and the occurrence of cardiovascular (CV) diseases 1 . Autoantibodies of the IgG subclass against apolipoprotein A1 (anti‐apoA1 IgG), the major apolipoprotein of HDL, have been shown to be an independent CV risk factor in the general population, as well as predictors of poor CV outcomes and overall mortality in most populations reported so far 2–11 . Translational investigations showed that anti‐apoA1 IgGs efficiently promote sterile inflammation, facilitate foam cell formation in vitro, and enhance the development of atherosclerosis and atherothrombosis in mice through specific innate immune receptors complexes and related signalling pathways 12–18 .…”
Section: Introductionmentioning
confidence: 99%
“…TLR2 engagement and subsequent activation have been shown to be required for autoantibodies against apoA-1 (anti-apoA-1 IgG) to mediate their pro-atherogenic effects (17)(18)(19)(20). Because anti-apoA-1 IgGs were shown to represent an independent cardiovascular (CV) risk factor associated with poor prognosis (21)(22)(23)(24)(25), to be elevated after viral infections (26,27), and to be preferentially oriented against the c-ter part of apoA-1 (28,29), we hypothesized that SARS-CoV-2 infection could elicit an anti-apoA-1 IgG response with substantial overlap with anti-SARS-CoV-2 IgG serology.…”
Section: Introductionmentioning
confidence: 99%